Building a Sustainable Governmental Public Health Workforce: A Look at the Millennial Generation. Issue 1 (January 2022) - Locke, Rachel; Gambatese, Melissa; Sellers, Katie; Corcoran, Elizabeth; Castrucci, Brian C.
Abstract : Context: Millennials have had a profound impact on society, the economy, and the US workforce. This study used generational definitions published by the Pew Research Center. Millennials includes respondents who reported an age between 21 and 36 years (born in 1981-1996) at the time the 2017 Public Health Workforce Interests and Needs Survey (PH WINS) was administered. Generation X includes respondents who reported an age between 37 and 52 years (born in 1965-1980), and the baby boom generation (baby boomers) includes respondents between 53 and 71 years of age (born in 1946-1964). Public sector agencies, including governmental public health, are increasingly interested in figuring out how to attract and retain millennials. As the governmental public health workforce anticipates upcoming retirements, knowledge about the motivations and organizational characteristics that appeal to millennials is crucial to understanding the millennial workforce and workplace dynamics for decades to come. In 2017, millennials made up 22% of the governmental public health workforce, Generation X 40%, and baby boomers 37%. Objective: This study examined opinions, expectations, and important workplace environment factors of millennials working in governmental public health compared with other generations. Design: We performed bivariate analyses and fit a logistic regression model to evaluate the association of generation with responses to a set of satisfaction and engagement PH WINS survey questions. Setting and Participants: Data were drawn from the 2017 PH WINS of governmental health department employees, including state health agency and local health department staff. PH WINS excludes local health departments with fewer than 25 staff members or serving fewer than 25 000 people. PH WINS included responses from 47 604 staff members, which reflected a 48% overall response rate. Results: The generations that were examined (millennials, Generation X, and baby boomers) were similarly satisfied with their jobs, organizations, and pay security, and millennials intended to leave their jobs for similar reasons as other generations. Millennials reported more strongly than other generations that their supervisors treated them with respect, that they had sufficient training to utilize technology, that their training needs are assessed, and that creativity and innovation were rewarded. They, however, reported less strongly that they were completely involved in their work and determined to give their best every day. Conclusions: Millennials in governmental public health agencies (excluding local health departments with <25 staff members or serving <25 000 people) may not be as different from other generations as previously thought. Governmental public health agencies should focus on highlighting workplace environment factors rated highly by millennials and on showcasing how careers in governmental public health could be attractive career options for millennials.